Tantangan Pembelajaran Pendidikan Agama Islam di Perguruan Tinggi Umum: Kebijakan dan Implementasi - Sudrajat, Tatang; Ruswandi, Uus; Arifin, Bambang Syamsul (Jurnal Pendidikan : Riset dan Konseptual, 2021)
Education plays an important role in shaping the character of the nation, especially religious education. Islamic religious education is part of general compulsory courses, including in non-religious universities. Its existence is regulated through laws and regulations at various levels of government. The implementation of the learning is faced with several challenges and problems. Through the data obtained by juridical normative, qualitative and literature methods, it is known that the challenges are related to the globalization era, students' perceptions of religious subjects, student educational background, the amount of SKS and learning time.